Cardiovascular magnetic resonance assessment of coronary flow reserve improves risk stratification in heart failure with preserved ejection fraction - Shingo Kato; Kazuki Fukui; Sho Kodama; Mai Azuma; Naoki Nakayama; Tae Iwasawa; Kazuo Kimura; Kouichi Tamura; Daisuke Utsunomiya (Journal of Cardiovascular Magnetic Resonance, 2021)
Abstract Background Coronary microvascular dysfunction (CMD) has been proposed as a novel mechanism for the pathophysiology of heart failure (HF) with preserved ejection fraction (HFpEF). Recent studies have suggested the potential utility of coronary flow reserve (CFR) as a marker of CMD in patients with HFpEF. Phase contrast (PC) cine cardiovascular magnetic resonance (CMR) of the coronary sinus has emerged as a non-invasive method to quantify CFR. We aimed to investigate the prognostic value of CMR-derived CFR in patients with HFpEF. Methods Data from 163 HFpEF patients (73 ± 9 years; 86 [53%] female) were retrospectively analyzed. Coronary sinus blood flow was measured in all patients, and myocardial blood flow was calculated as coronary sinus blood flow divided by left ventricular mass. CFR was calculated as the myocardial blood flow during adenosine triphosphate infusion divided by that at rest. Adverse events were defined as all-cause death and hospitalization due to HF exacerbation. Event-free survival stratified according to CFR < 2.0 was estimated with Kaplan–Meier survival methods and Log-rank test. Results During a median follow-up of 4.1 years, 26 patients (16%) experienced adverse events. CMR-derived CFR was significantly lower in HFpEF with adverse events compared with those without (1.93 ± 0.38 vs. 2.67 ± 0.52, p < 0.001). On a Kaplan Meier curve, the rates of adverse events were significantly higher in HFpEF patients with CFR < 2.0 compared with HFpEF with CFR ≥ 2.0 (p < 0.001). The area under the curve of CFR for predicting adverse events was significantly higher than that of LGE (0.881 vs. 0.768, p = 0.037) and GLS (0.881 vs. 0.747, p = 0.036). Conclusions CFR assessed using coronary sinus PC cine CMR may be useful as a non-invasive prognostic marker for HFpEF patients.